Homeodomain-interacting Protein Kinase-2 Stabilizes p27(kip1) by Its Phosphorylation at Serine 10 and Contributes to Cell Motility - Pierantoni, Giovanna Maria (American Society for Biochemistry and Molecular Biology, 2011)
HIPK2 is a serine/threonine kinase that acts as a coregulator of an increasing number of factors involved in cell survival and proliferation during development and in response to different types of stress. Here we report on a novel target of HIPK2, the cyclin-dependent kinase inhibitor p27(kip1). HIPK2 phosphorylates p27(kip1) in vitro and in vivo at serine 10, an event that accounts for 80% of the total p27(kip1) phosphorylation and plays a crucial role in the stability of the protein. Indeed, HIPK2 depletion by transient or stable RNA interference in tumor cells of different origin was consistently associated with strong reduction of p27(kip1) phosphorylation at serine 10 and of p27(kip1) stability. An initial evaluation of the functional relevance of this HIPK2-mediated regulation of p27(kip1) revealed a contribution to cell motility, rather than to cell proliferation, but only in cells that do not express wild-type p53.